Effects of Supplementation with Corn or Dried Distillers Grains on Gains of Heifer Calves Grazing Smooth Bromegrass Pastures - L. W. Lomas; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 90 heifer calves grazing smooth bromegrass pastures were used to compare supplementation with 0.5% of body weight per head daily of corn or dried distillers grains (DDG) in 2014, 2015, and 2016. Daily gains of heifers supplemented with corn or DDG were similar (P>0.05).
Keywords: distillers grains; grazing; supplementation; bromegrass; stocker cattle; protein